CORPORATE BOARD SIZE AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AMONG LISTED INDUSTRIAL GOODS COMPANIES IN NIGERIA - Jimoh IBRAHIM; Emmanuel Taiwo AINA; Olubukola Olajumoke AKANJI (Malete Journal of Accounting and Finance)
The failure of the board of directors to effectively manage a company's disclosure of CSR can significantly damage its reputation. Therefore, this study examines the influence of board size on corporate social responsibility disclosure (CSRD) among listed industrial goods companies in Nigeria. Ex post facto research design was used. Purposive sampling technique was used to select sample size of eleven (11) quoted industrial goods companies out of study’s population of 13 quoted firms. Secondary data were extracted from annual accounts of sampled 11 companies from 2011-2021. The study utilized panel estimation regression methods to analyze the data. The results indicated that board size had a positive and significant effect on CSR disclosure (coeff.= 0.0154, p-v =0.0260), suggesting that a diverse board with more expertise, qualities, and core competence can enhance monitoring and supervision, thereby improving the quality of CSR. The study's concluded that corporate boards can effectively encourage listed industrial products companies in Nigeria to disclose their CSR practices. The study also recommends that industrial products companies should maintain an effective board size to oversee management and ensure that all actions align with the company's objectives.